Rice leaf rolling under drought conditions is not a selection criteria for drought tolerance - CGIAR Research Program on Rice (2019)
Our conclusions provide direct guidance to breeders conducting visual selection for drought tolerance. We have published our results as an open access journal article, and the data is publically available on Dataverse.